International Criminal Protection of the Environment: Advancing Towards the Crime of Ecocide - Martín Aragón, María del Mar (2024)
This study focuses on three fundamental aspects related to the international protection of the environment. Thus, after a brief overview of the environmental situation concerning the climate emergency we face, the issue of the environment as a human right is addressed. Subsequently, the historical development of ecocide in the context of the United Nations is examined. Finally, there is an in-depth analysis of the proposed definition of ecocide and the modifications suggested for the Rome Statute, highlighting the work of the Stop Ecocide Foundation and other similar proposals. This approach aims to contribute to the development of international environmental criminal protection by exploring these three central axes.